Penerapan Manpower Planning (MPP) dan Full Time Equivalent (FTE) pada Bagian Produksi PT. Lampung Sukses Bersama (Lampung Banana Foster) - Tia Riski Rahmadhani; Eristia Arfi (Department of Mathematics, Faculty of Science and Technology Universitas Jambi, 2024)
PT. Lampung Sukses Bersama, commonly known as Lampung Banana Foster, is a specialized retail establishment dedicated to promoting indigenous Nusantara products, particularly those hailing from the Lampung region. The core values of Lampung Banana Foster revolve around ensuring top-notch product quality, premium service, and a modern aesthetic. In line with its organizational strategy, it places significant emphasis on the importance of effective human resource management. Through empirical research, a noticeable misalignment between available human resources and actual production output has been uncovered. The research data, focuses on the production output of the production department from April to June 2020, coinciding with the emergence of the Covid-19 pandemic and its consequential impacts on business operations. Analysis of this dataset highlights a significant disparity between employee headcount and Full-Time Equivalent (FTE) value. Using the framework of Manpower Planning (MPP), the study reveals that shortages in employee numbers vary on a monthly basis. Consequently, we suggest that augmenting the workforce through new employee recruitment is necessary to ensure an equitable distribution of workload among all staff members. This finding underscores the importance of strategic human resource interventions to maintain operational efficiency and organizational resilience amidst changing circumstances.